Georgia Architectural and Historic Properties Survey of Rural [237] South western section of county, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [237] South western section of county, Valdosta, Ga. December 1980. A one story rectangular plan with gabled roof and clapboard siding. Sash windows with 2/2 lights. Alcove has been filled in and gabled portico added. Additional building, small L-shaped gabled tin roof, brick piers, exposed rafters. Poor condition. c. 1900. A typical rural church common to this area.
Georgia Architectural and Historic Properties Survey of Rural [237] South western section of county, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.7 MB (83,597,180 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)